Debt and Online Loan Management Counseling for the Village Community of Dedeul, Taraju District, Tasikmalaya Regency - Dyah Ciptaning Lokiteswara Setya Wardhani (Indonesian Journal of Society Development, 2024)
The use of online loans in West Java has increased in recent years, providing easy access to funds but also increasing the risk of unmanaged debt. This community service program aims to improve the financial literacy of villagers and provide education on debt management and the risks of online loans. The implementation of the service was carried out through counseling involving various elements of society. The results showed a significant increase in the understanding and awareness of residents regarding the importance of good financial management. Residents began to implement more effective debt management strategies and showed a decrease in interest in online loans. However, challenges in long-term implementation remain, indicating the need for ongoing follow-up and support from the government and local financial institutions. This service emphasizes the importance of collaboration between various parties to ensure that positive changes in the financial management of the Dedeul Village community can last and contribute to their welfare in the future